2013
DOI: 10.1074/jbc.m113.465088
|View full text |Cite
|
Sign up to set email alerts
|

Dynein Interacts with the Neural Cell Adhesion Molecule (NCAM180) to Tether Dynamic Microtubules and Maintain Synaptic Density in Cortical Neurons

Abstract: Background: Dynein is a microtubule motor that can also tether dynamic microtubule plus-ends. Results: Neural cell adhesion molecule isoform-180 (NCAM180) binds directly to dynein, facilitating microtubule tethering at the cortex and enhancing cell-cell adhesion and synaptic density. Conclusion:The dynein-NCAM180 interaction contributes to the maintenance of synaptic density in cortical neurons. Significance: Dynein functions as both microtubule motor and microtubule tether in neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 72 publications
1
39
0
Order By: Relevance
“…For example, in non-neuronal cells cortical dynein located just below the cell membrane captures peripheral microtubules, induces catastrophe events and microtubule shortening, and thereby generates pulling forces upon the linked microtubule network [142]. In neurons, dynein has been proposed to target microtubules to actin networks at the cell edge either through the formation of a lissencephaly 1 (Lis1)-dynactindynein +TIP complex or through interaction with the cell-surface receptor neuronal cell adhesion molecule (NCAM) [143,144] ( Figure 3C). Analogous to the zippering of microtubules along actin filaments (discussed in the +TIPs section), microtubules can also engage and polymerise along other microtubules, guided by motor-protein-containing +TIP complexes such as EB1-APC-kinesin2 [145][146][147].…”
Section: Motor-protein-mediated Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in non-neuronal cells cortical dynein located just below the cell membrane captures peripheral microtubules, induces catastrophe events and microtubule shortening, and thereby generates pulling forces upon the linked microtubule network [142]. In neurons, dynein has been proposed to target microtubules to actin networks at the cell edge either through the formation of a lissencephaly 1 (Lis1)-dynactindynein +TIP complex or through interaction with the cell-surface receptor neuronal cell adhesion molecule (NCAM) [143,144] ( Figure 3C). Analogous to the zippering of microtubules along actin filaments (discussed in the +TIPs section), microtubules can also engage and polymerise along other microtubules, guided by motor-protein-containing +TIP complexes such as EB1-APC-kinesin2 [145][146][147].…”
Section: Motor-protein-mediated Interactionsmentioning
confidence: 99%
“…(C) Microtubule exploration of adhesion sites is facilitated after coupling of cell-adhesion molecules (CAMs), such as NCAM and N-cadherin, with the actin network and a resulting attenuation of retrograde flow (1)[81]. The association of +TIPs or dynein either directly or indirectly with the actin cortex can lead to microtubule capture at the cell edge(2) [143,144]. Symbols are listed in the figure key, otherwise colouring as forFigure 1: brown area, growth cone C-domain; peach area, growth cone T-domain; pale yellow area, growth cone P-domain.…”
mentioning
confidence: 99%
“…We showed that the abundance of ␣1-2Fuc glycan associated with NCAM is diurnal, although the expression of Ncam1 mRNA and NCAM protein does not vary. NCAM functions in neurite outgrowth and synaptic formation, especially in the OB and hippocampus (37), and it is a highly glycosylated protein with multiple types of glycan (38,39). NCAM-180 contributes to the maintenance of synaptic formation (39), and OB development is defective in NCAM-180 knock-out (40), as in FUT1 knock-out (25) mice.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, glycoconjugates including α1-2Fuc glycan are located in both local circuits of the MOB and the secondary pathway of the olfactory system. Neural cell adhesion molecule (NCAM) is a highly glycosylated protein [Liedtke et al, 2001] and is apparently the main core protein of α1-2Fuc glycan in the mouse olfactory bulb [Pestean et al, 1995;Murrey et al, 2009;Kondoh et al, 2014]; it plays critical roles in neurite outgrowth and synaptic formation, especially in the olfactory bulb [Treloar et al, 1997;Zamze et al, 1998;Perlson et al, 2013]. Because α1-2Fuc glycan also mediates neuronal functions and affects neuronal morphology [Pohle et al, 1987;Krug et al, 1991Krug et al, , 1994Matthies et al, 1996;Lorenzini et al, 1997;Kalovidouris et al, 2005;Murrey et al, 2006], α1-2Fuc attachments might affect NCAM function and mediate both major adjustments within the olfactory pathway and minor adjustments within the MOB.…”
Section: Uea-i Reaction In the Aobmentioning
confidence: 99%